AS AN URBAN PLANNING PROBLEMATIC CULTURE AND CITY - Kurtarir, Erhan; Okten, Ayse Nur (YILDIZ TECHNICAL UNIV, 2015)
Urban planning and 'culture' relation has been analysed by numerous works and study from different perspectives. This article's and dissertation's perspective about relation of culture-place-planning has been evaluated in limited number of studies. Especially there isn't satisfactory studies that evaluating faith and space relation in Turkish planning literature. This work basically evaluating culture and place relation by faith and places of worships conceptual frameworks. It will be evaluated that importance and necessity of sustainable cultural identity.
Keywords: Urban planning policies; cultural identity; space and place.; Engineering